Is it wrong to try to pick up girls in a dungeon? on the side. 10, Sword oratoria - Omori, Fujino (Yen Press, 2020)
"Loki Familia has reached the unknown 59th Floor, and it's not quite what they expected. A corrupted spirit, composed of other spirits devoured by monsters, lies before them, and for some reason, it's calling Aiz 'Aria'..."--Provided by publisher.